1997
DOI: 10.1097/00004872-199715090-00007
|View full text |Cite
|
Sign up to set email alerts
|

Is the absence of a normal nocturnal fall in blood pressure (nondipping) associated with cardiovascular target organ damage?

Abstract: Objective To determine whether the failure to decrease blood pressure normally during sleep is associated with more prominent target organ damage.Methods Cardiac and vascular structure and function were characterized in 183 asymptomatic, unmedicated hypertensive patients and compared with their ambulatory blood pressures. ResultsThe 104 patients with a normal (> 10%) nocturnal fall in systolic blood pressure (dippers) were similar to the 79 patients with an abnormal fall (nondippers) in sex, race, body size, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 38 publications
2
53
1
2
Order By: Relevance
“…Many researchers have evaluated cardiac damage in untreated individuals with essential hypertension and found no significant differences between dippers and nondippers with respect to LV diameter (14,21), LV systolic and diastolic function (21), interventricular septum thickness, posterior wall thickness, relative wall thickness (14,45,56), LV concentric remodelling (45,56), LVH, LVM and LVMI (14,21,45,56), aortic distensibility (21) and atrial dimensions (56). However, in these studies, the classification of dipping status was based on a single ABPM session.…”
Section: Cardiac Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have evaluated cardiac damage in untreated individuals with essential hypertension and found no significant differences between dippers and nondippers with respect to LV diameter (14,21), LV systolic and diastolic function (21), interventricular septum thickness, posterior wall thickness, relative wall thickness (14,45,56), LV concentric remodelling (45,56), LVH, LVM and LVMI (14,21,45,56), aortic distensibility (21) and atrial dimensions (56). However, in these studies, the classification of dipping status was based on a single ABPM session.…”
Section: Cardiac Geometrymentioning
confidence: 99%
“…Several studies involving subjects with uncomplicated essential hypertension have revealed an association between a nondipper BP profile and an increased risk of target organ damage at the cardiac, renal, vascular and cerebrovascular levels (6,9,10,15,18,27,28,(42)(43)(44)(45). Target organ damage has also been found to be linked with two additional abnormal BP patterns: reverse dipping (nocturnal rise in night-time BP) and extreme dipping (nocturnal fall in night-time BP of greater than 20%) (46).…”
mentioning
confidence: 99%
“…Some authors demonstrated that nondipping status was associated with greater cardiac and extracardiac TOD, [17][18][19] whereas other studies failed to demonstrate any significant difference in left ventricular and vascular structure among dippers and nondippers. 20,21 Contradictory results can be attributed to a variety of clinical and methodological problems. The classification into dippers and nondippers based on a single ABPM represents probably one of the major confounding factors because of the limited reproducibility of nocturnal BP fall over time.…”
Section: Introductionmentioning
confidence: 99%
“…In a larger group of unmedicated hypertensive patients, 20 non-dippers were more likely to have carotid plaque and an increased common carotid intima-media thickness, although adjustment for age rendered these differences insignificant and there-fore the lack of a nocturnal fall in BP was not associated with carotid arterial disease, independently of age. When Roman et al 20 analysed the data separately for men and women, results did not change substantially and the small differences observed between female dippers and non-dippers were again eliminated after controlling for age.…”
Section: Discussionmentioning
confidence: 85%
“…18 It has been recently observed that in hypertensive patients who did not show a decrease of BP during night time the intima media thickness of the common carotid artery was greater as compared with patients with a sleep reduction of BP. 19,20 In the present population-based cross-sectional study, designed to estimate the prevalence of structural changes both in the heart and in the carotid arteries in middle-aged subjects, the carotid intimamedia thickness and the presence of plaque, as well as the presence of LVH, were determined in relation to an altered diurnal BP rhythm, obtained by ambulatory monitoring, before and after correction for other traditional risk factors.…”
Section: Journal Of Human Hypertension (2001) 15 879-885mentioning
confidence: 99%